2018
DOI: 10.21834/ajbes.v3i9.74
|View full text |Cite
|
Sign up to set email alerts
|

Women and Crime in Central Business District Area

Abstract: Crime in the central business district has gain momentum over several years. With the increasing of a non index crime in Malaysia, it has also indirectly increase the chances of becoming a crime victim among women. Thus, this study intended to examine the exact crime incident area in the city centre that will affect the working women who depend on stage bus to commute. Result shows that most crime occur while walking and waiting at the bus stop. A high level of unsafe were spotted, when they rated a higher dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…There is evidence from all over the world particularly the developing countries to prove this claim. Multiple studies from India show that Indian women face various types of harassments even during day time [12]. This study further states that 51.4% of surveyed women by Jagori organization reported to have faced harassment while using public transit.…”
Section: ) the Barrierssupporting
confidence: 64%
See 1 more Smart Citation
“…There is evidence from all over the world particularly the developing countries to prove this claim. Multiple studies from India show that Indian women face various types of harassments even during day time [12]. This study further states that 51.4% of surveyed women by Jagori organization reported to have faced harassment while using public transit.…”
Section: ) the Barrierssupporting
confidence: 64%
“…This study further states that the results of a survey conducted in the Los Angeles city shows that bulk of the car owners would use public transport if they believed it is safe and clean [15]. Likewise, another research identified that women felt unsafe when the services are not comfortable, while waiting for long times at bus stations, when the safety measures are not properly indicated and when there is lack of information about bus services [12]. In some studies women are reported to feel less fear while the vehicles are not empty and they witness the presence of additional staff.…”
Section: ) the Barriersmentioning
confidence: 63%
“…The lack of research on women's transit safety is not exclusive to Brazil but it is a more general problem found elsewhere as well (Can, 1995;Gekoski et al, 2015;Madan and Nalla, 2015;Natarajan, 2016;Seedat et al, 2006;Sham et al, 2013) This article aims at contributing to this area of research by assessing the nature, the levels and the patterns of sexual crimes against women (cases of staring, touching, groping, ejaculation, exposing genitalia and full rape) in the São Paulo metro system, the largest rapid transit system in Brazil, and the second largest in South America. The analysis is performed by comparing reported data with records of other types of crimes in the subway system in time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies observed that perceived pedestrian satisfaction became tormented by a few factors. The phrase "satisfaction" has been defined as an accumulative construct to be able to affect respondents' expectations and perceptions of performances at any time (Sham et al, 2018). In this point, the pedestrian delight of pedestrian walkways is related to the notion of having safety features walkways assembly as much as humans' expectancies and opens up a possibility to crime and judging it based on how fulfilling it is closer to on walker desires in urban areas.…”
Section: Problem Statementmentioning
confidence: 99%